Resilience in the Face of Adversity : African American Women’s Experiences of Discrimination - BERESSA, LAMIA SAMIHA (My University, 2023)
Discrimination against African-American women is a widespread and long-standing issue with far-reaching consequences for their lives, well-being, and opportunities for advancement and achievement. Throughout history, African-American women have faced many forms of discrimination, some more subtle than others. These forms of discrimination have significantly shaped their experiences and limited their potential for their growth. This dissertation aims to explore the challenges posed by discrimination against African-American women by shedding light on its historical context, the various types of discrimination they face, and understanding its deep impact on their physical and psychological health, as well as the strategies used to cope with it. The findings reveal that African-American women face different forms of discrimination, which has important physiological and psychological impacts. They employ assimilation and resistance coping methods to navigate discrimination. By exploring these elements, we can promote a stronger sense of understanding and empathy and inspire positive changes toward a more welcoming society in which African-American women can succeed without the burdens of discrimination.
Keywords: Racism; Descrimination; African American Women; Coping. mechanisms; Stereotyping; Physiological and psychological impact